Molecular characterization of Citrus tristeza virus strains in Peninsular Malaysia - Ayazpour, Kavous; Sijam, Kamaruzaman; Vadamalai, Ganesan; Jaafar, Hawa Z. E. (Academic Journals, 2011)
Sixty Malaysian CTV isolates were characterized by bi-directional polymerase chain reaction (BD-PCR) and restriction fragment length polymorphism (RFLP) analysis of their coat protein (CP) gene. In BD-PCR analysis, 392-bp fragments were amplified from seven isolates. The other 53 isolates produced only 320-bp fragments. RFLP patterns of RT-PCR products of CP gene digested with HinfI restriction enzyme were similar to I-IV, VI-VII and two new groups. Isolates AMK1, AMJ12, AMT38, AMT39 and AMT43 could not be classified when they were compared to any standard CTV digest pattern. These isolates produced a unique restriction pattern with two fragments of 210 and 300 bp and isolate AMI61 produced different restriction pattern with three fragments of about 100, 270 and 300 bp. Therefore these isolates were designated as Groups IX and X. These results suggest that CTV populations in Malaysia contain new genetic variants.